2020
DOI: 10.3390/ijerph17041393
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Traffic Volume and Accident Frequency at Intersections

Abstract: Driven by the high social costs and emotional trauma that result from traffic accidents around the world, research into understanding the factors that influence accident occurrence is critical. There is a lack of consensus about how the management of congestion may affect traffic accidents. This paper aims to improve our understanding of this relationship by analysing accidents at 120 intersections in Adelaide, Australia. Data comprised of 1629 motor vehicle accidents with traffic volumes from a dataset of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 42 publications
4
19
1
1
Order By: Relevance
“…This study also shows that increases in collisions are more likely as more vehicles break speed limit rules. This study's results do not reflect the same linear-to-nonlinear relationship between accidents and traffic levels as [71,72]. At low to mid traffic densities, collisions increase disproportionately as traffic density increases.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This study also shows that increases in collisions are more likely as more vehicles break speed limit rules. This study's results do not reflect the same linear-to-nonlinear relationship between accidents and traffic levels as [71,72]. At low to mid traffic densities, collisions increase disproportionately as traffic density increases.…”
Section: Discussioncontrasting
confidence: 80%
“…This study also suggests that lower traffic density on average leads to fewer collisions regardless of adherence levels, as was observed in [72]. However, as adherence decreases, this leads to increased collisions relative to the number of vehicles in the urban environment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The hypothesis behind this work was the assumption that at least the crash frequency that involves two cars should be a second-order polynomial function of the traffic flow [30]. A similar idea is also proposed in [27,31].…”
Section: Motivationmentioning
confidence: 98%
“…The relationship has not been studied as extensively for car accidents in urban and suburban settings. One observational study monitoring 120 signal intersections in Adelaide, Australia found that car accident counts increase with hourly traffic volumes, with an especially sharp increase at very high traffic volumes [19]. For pedestrian accidents, empirical studies have limited temporal resolution, but existing work suggests that annual accident rates correlate with average annual traffic volumes in an approximately linear way [20,9].…”
Section: Introductionmentioning
confidence: 99%